Digital identity and Social Work in Spain: analysis of the microinfluencer phenomenon on Instagram - Muriel-Saiz, Mercedes; Castaño-Ortega, Tarsila; Martín-Estalayo, Maribel; Cebolla-Bueno, Óscar (Prospectiva. Revista de Trabajo Social e Intervención Social, 2023)
The purpose of this article is to contribute to the study of social networks as a space for the dissemination of the profession and discipline of social work. From the content analysis of the ten professional profiles with more followers on Instagram and recognized within the microinfluencer phenomenon in the Spanish geography, the most characteristic features of digital identity, audiovisual content, and epistemological and ethical conceptions that are identified and disseminated of social work are described. Although it is an urgent task to establish bridges and complicities between communication and social work to favor the dissemination of the area of knowledge and professional experience, the risks and consequences derived from these digital practices should not be ignored. The modes of production are not alien to the current neoliberal and mercantile context, where the social has become a business space and, sometimes, professional objectives are more subordinated to the means than to the end.